Physicochemical And Microbial Stability Of Wheat Bread As Influenced By The Supplementation Of Radiofrequency Stabilized Rice Bran (Applied Biological Research, 2020)
The present study was aimed to assess the suitability of radiofrequency treated rice bran supplementation in wheat bread. The refined wheat flour  was blended with radiofrequency stabilized rice bran in varying  proportions (100:0, 95:5, 90:10, 85:15, 80:20, 75:25 and 70:30) and the  formulated breads were assessed for their physicochemical and microbial  characteristics. The bread with 30% stabilized rice bran supplementation  showed highest crude protein (13.48%), crude fat (6.69%) and crude fiber  (3.60%) contents, whereas control treatment(100% wheat flour) had lowest  crude protein (11.64%), crude fat (2.43%) and crude fiber (1.56%) content.  Loaf weight, redness (a*) and yellowness (b*) of the formulated breads  increased with increase in stabilized rice bran; while loaf volume, specific  volume, crust to crumb ratio and L* value decreased with the addition of  stabilized rice bran. The supplementation of stabilized rice bran increased  total bacterial and yeast and mould counts of bread from 2.84 × 104 to 3.19  × 104 and 1.49 × 104 to 1.84 × 104 cfu g-1, respectively. During storage period  of 4 days, microbial count and yeast and mould count of breads increased from 0.34 × 104 to 6.41 × 104 and 0.25 × 104 to 3.32 × 104 cfu g-1, respectively.  It may be concluded that supplementation of rice bran up 20% enhanced  nutritional and overall acceptability scores.
Keywords: Microbial load; radiofrequency; redness; rice bran; yellowness